Melk facilitates pulmonary artery smooth muscle cell proliferation and migration in pulmonary hypertension via modulation of YAP/TAZ signaling - Yang, Qiang; Chen, Peisheng; He, Xiaoxia; Jian, Jingting; He, Miaomiao; Lin, Tianxiao; Zheng, Shaoqiang; Liu, Degang (Frontiers in Cell and Developmental Biology, 2025)
Pulmonary arterial hypertension (PAH) is characterized by progressive pulmonary arteriolar constriction and remodeling, leading to elevated vascular resistance and right heart failure. Aberrant proliferation, migration, and phenotypic switching of pulmonary artery smooth muscle cells (PASMCs) are central to this process. Maternal embryonic leucine zipper kinase (MELK), a serine/threonine kinase of the AMPK family, is known to regulate cell cycle and tumorigenesis, but its role in PAH remains unclear. MELK expression was elevated in PASMCs from patients with PAH, in PDGF-BB–stimulated human pulmonary artery smooth muscle cells (HPASMCs), and in PASMCs of Su/H mouse lungs, indicating conserved upregulation across human and experimental models. In vitro, pharmacological inhibition or genetic silencing of MELK suppressed DNA synthesis, proliferation, and migration of HPASMCs under basal and PDGF-BB–stimulated conditions, concomitant with downregulation of PCNA and Cyclin D1. Conversely, MELK overexpression promoted PASMC growth and migration and accelerated the transition from a contractile to a synthetic phenotype. Mechanistically, MELK reduced YAP phosphorylation (Ser127), thereby activating Hippo–YAP/TAZ signaling and increasing downstream effectors (CYR61, CTGF, Birc5, Cyclin E), while leaving upstream gene transcription unchanged. The YAP inhibitor Verteporfin blunted MELK-driven PASMC proliferation and migration, underscoring the central role of YAP/TAZ signaling. Finally, in vivo pharmacological inhibition of MELK by OTS167 markedly reduced right ventricular systolic pressure, hypertrophy, and pulmonary vascular remodeling in Su/H mice, confirming the therapeutic relevance of MELK targeting in PAH. Collectively, these findings identify MELK as a novel regulator of PASMC pathobiology in PAH and suggest that it may represent a potential therapeutic target.